Ідентифікація закономірності у вібраціях об’єкта для діагностики та прогнозування стану - Сільвестров, Антон Миколайович; Скринник, Олексій Миколайович; Уманська, Катерина Вікторівна (НТУ "ХПІ", 2013)
The article deals with diagnosis and prediction of machine working capacity by acoustic signals. Creation of a single analytical model is proposed. The method proposed partial models should be combined into a single analysis, by multiplying their analytic in the whole range of variables object weight functions - the equivalent of frequency filters. Technical state prediction of this or that element of the machine to the value of the original function of the amplitude of the acoustic signal.

В роботе рассмотрен вопрос диагностики и прогнозирования работоспособности машин по акустическим сигналам. Предложено построение информативной аналитической зависимости структурного параметра от диагностического признака, методом кусочно-аналитического описания простых локальных моделей, помноженных каждую из них на аналитическую во всем диапазоне весовую функцию, и объединение их в единую аналитическую модель путем сложения. В дальнейшем оценивание состояния того или иного элемента машины по значению производной функции амплитуды акустического сигнала.
Identification of patterns in the vibration of object for diagnosis and technical state prediction
Keywords: граничні характеристики вібрацій; залишковий ресурс роботи; амплітуда акустичного сигналу; період інтенсивного зносу; накопичення утомних напруг; метод кусково-аналітичного опису